Exploring the concept of surgical transition: surgical activity in the light of economic development in Sierra Leone, Liberia, Ghana and India - Juul M. Bakker; Juul M. Bakker; Alex J. van Duinen; Alex J. van Duinen; Alex J. van Duinen; Alex J. van Duinen; Priti Patil; Priyansh Nathani; Priyansh Nathani; Adam Gyedu; Adam Gyedu; Håvard A. Adde; et al. (Frontiers in Surgery)
IntroductionThe surgical volume indicator measures surgical activity within a population, but it does not fully untangle the details behind the statistical indicator. As health systems evolve and countries develop economically, the types of surgeries performed, providers, and levels of healthcare facilities may provide a richer understanding of changes in surgical activity. This research studied surgical activity in four diverse settings by analyzing initial data to assess trends in patient characteristics, surgical staff, case distribution, level of care, and anesthesia practices, forming the basis for a “surgical transition” framework.MethodsWe conducted a secondary analysis of surgical volume data from four studies in Sierra Leone, Liberia, Ghana, and India, to assess trends in surgical distribution. Descriptive statistics were used to compare surgical volumes by population subgroups, surgical providers, case distribution, level of care, and anesthesia.ResultsFindings show that countries with higher GDP per capita had greater surgical volumes, more specialist providers, and a broader, more advanced case mix. Increases in surgical volume were most notable among older age groups, gender disparities in access diminished as systems developed. In lower-income settings, a large share of surgeries were cesarean sections or other procedures for women of reproductive age, while there were more surgeries in the older population in more advanced economies. The proportion of essential surgeries, including for example surgeries for obstetric complications, abdominal emergencies and injuries, remained stable between low- and lower-middle-income countries, decreasing only with further economic development. Specialist-performed procedures increased with economic growth, resulting in greater surgical variety and complexity.DiscussionChanges in surgical volume must be understood within the broader context of societal and economic development as well as the health system. The concept of “surgical transition” highlights how demographic and socioeconomic progress is reflected in the quantity, diversity, and complexity of surgical services. As countries advance, internal priorities, such as healthcare policies, financing, infrastructure, and service delivery mechanisms, also evolve. These factors influence surgical care delivery. Each phase of the surgical transition presents different challenges and needs. Recognizing the phase of surgical transition can help guide strategies and establish realistic interim targets for the global surgical indicators, making them more actionable tools for measuring progress and comparing systems.